The Effect of Using Google Classroom and Whatsapp Group Applications on Students’ Interest and Learning Outcomes in Chemistry During The Covid-19 Pandemic - mustapa, Kasmudin; Ahyar, Aditya Kurniawan; Ratman, Ratman; Magfirah, Magfirah (Universitas Negeri Malang, 2022)
This study aimed to determine the effect Google Classroom and WhatsApp Group applications on the interest and learning outcomes in chemistry during the Covid-19 pandemic at SMA Negeri 1 Ampibabo. It was a quasi-experimental study. The sample was students of class X MIA D and X MIA E for the 2021/2022 academic year, totaling 66 students. The interest in learning and learning outcomes were tested statistically using analysis t-test two parties. The results of data analysis showed that the mean score of student learning outcomes in the experimental class was 78.5, while in the control class was 86. The data analysis of questionnaires on students’ learning interest showed that the experimental class was in a